Medical resource use and expenditure in patients with chronic heart failure: a population‐based analysis of 88 195 patients. (25th April 2016) - Farré, Nuria; Vela, Emili; Clèries, Montse; Bustins, Montse; Cainzos‐Achirica, Miguel; Enjuanes, Cristina; Moliner, Pedro; Ruiz, Sonia; Verdú‐Rotellar, Jose Maria; Comín‐Colet, Josep
Abstract : Aims: Heart failure (HF) is one of the diseases with greater healthcare expenditure. However, little is known about the cost of HF at a population level. Hence, our aim was to study the population‐level distribution and predictors of healthcare expenditure in patients with HF. Methods and results: This was a population‐based longitudinal study including all prevalent HF cases in Catalonia (Spain) on 31 December 2012 ( n = 88 195). We evaluated 1‐year healthcare resource use and expenditure using the Health Department (CatSalut) surveillance system that collects detailed information on healthcare usage for the entire population. Mean age was 77.4 (12) years; 55% were women. One‐year mortality rate was 14%. All‐cause emergency department visits and unplanned hospitalizations were required at least once in 53.4% and 30.8% of patients, respectively. During 2013, a total of €536.2 million were spent in the care of HF patients (7.1% of the total healthcare budget). The main source of expenditure was hospitalization (39% of the total) whereas outpatient care represented 20% of the total expenditure. In the general population, outpatient care and hospitalization were the main expenses. In multivariate analysis, younger age, higher presence of co‐morbidities, and a recent HF or all‐cause hospitalization were independently associated with higher healthcare expenditure. Conclusions: In Catalonia, a large portion of the annual healthcare budget is devoted to HF patients. Unplanned hospitalization represents the main source of healthcare‐related expenditure. The knowledge of how expenditure is distributed in a non‐selected HF population might allow health providers to plan the distribution of resources in patients with HF.